EVALUASI PELAYANAN AIR MINUM DISTRICT METER AREA (DMA) DARUSSALAM PADA PDAM TIRTA DAROY KOTA BANDA ACEH - Buraida, Buraida (JURNAL TEKNIK SIPIL, 2022)
Abstract: The still high water loss in PDAM Tirta Daroy which reached 34.50% and the disruption of the only raw water source, namely the Krueng Aceh River, became an important issue that disrupted clean water services to the community. This research is a case study by conducting data analysis and interviews to determine the quality, continuity, and quantity of clean water from PDAM Tirta Daroy in the District Meter Area (DMA) Darussalam. In data processing using descriptive method. The results showed that after the Gampong Darussalam DMA Program was carried out at the end of December 2018, positive results were obtained as indicated by the water sold increased by 33%, the average water consumption per house connection increased by 30%, the number of active customers increased by 1.09%, Revenue increased 29.96%, Non Revenue Water (NRW) or water loss decreased by 13%, water pressure in pipelines increased 16 times and the number of customer complaints decreased. However, different results are shown in the field data collection carried out 2 years later (October 2021) where the water loss increased again to 40.80%, close to the figure before the DMA program was implemented. Good technical planning is not enough, PDAM Tirta Daroy must also have non-technical plans for the implementation of DMA, such as related to the structure in charge of the District Meter Area, funding budget plan, Standard Operating Procedures, and more detailed targets for reducing water loss every year, so that a good plan can be operated and executed properly as well.Keywords : PDAM Tirta Daroy, DMA Darussalam, water loss